Keanekaragaman Spesies Arthropoda di Badan Air dan Sekitar Mata Air Kecamatan Gunungpati, Kota Semarang: Diversity of Arthropod Species in Water Bodies and Around Springs in Gunungpati District, Semarang City - Novianti, Ira; Nana Kariada Tri Martuti; Partaya; Sri Ngabekti (Universitas Negeri Semarang, 2025)
Arthropods are the largest phylum in the Animalia kingdom that can live on land, in freshwater, in the sea, or in the air. Springs are bodies of water that seep out through cracks in rocks to the surface of the ground, serving as a habitat for various Arthropods and the Gunungpati district has several springs in its area. This study aims to analyze the diversity of arthropod species and to describe the abiotic and biotic factors that influence the diversity of arthropod species in the water bodies and around the springs in the Gunungpati district, Semarang City. The research was carried out from October to December 2022, located at five springs, among others. The research was conducted from October to December 2022 at five springs, namely Sendang Jedung, Sendang Lanang Trangkil, Sendang Ndelik, Sendang Mbiru, and Sendang Gede. The data collection method was purposive sampling. The approach used in this research is a quantitative approach with a descriptive research type. The research results showed a total of 1537 individuals and 112 species of arthropods, which included 146 individuals in water bodies and 1391 individuals around springs. The diversity index ranged from moderate to high, between 1.82-3.30. The dominance index values were low, ranging from 0.05-0.29, and the evenness index values fall within moderate to high criteria, ranging from 0.52-0.86. The Sorenson similarity index on the five ponds is considered low. Abiotic factors do not affect diversity too much because it has similar values in the five springs. Therefore, biotic factors (organic matter, litter, and surrounding vegetation) greatly influenced the diversity of arthropod species in water bodies and around the spring in Gunungpati District, Semarang City.